Food and environmental behavior in times of the confinement by Covid-19, Apurímac, Peru - Huaraca Aparco, Rosa; Delgado Laime, María del Carmen; Tadeo, Fidelia Tapia; Pardo, Fredy Taípe; Camacho, Juan Alarcón (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Thechange in eating habits and responsible production systems leads to reduced environmental impact. The objective of this research was to study dietary and environmental behavior in university students in Andahuaylas province during the confinement of Covid-19. The study was cross-cutting through the use of data collected online through an anonymously resolved questionnaire, scheduled from July 18 to August 30, 2020 in the Apurímac-Peru region. In which 390 undergraduate students between the age of 18 and 28 participated. The questionnaire was divided into 03 sections: sociodemographic characteristics, dietary practices and environmental-related behavior during covid-19 confinement. In the study se found that 65.8% of students reported healthier dietary practices during covid-19confinement, in terms ofgender, women consistently consumed tubers (85.7%), vegetables (73.5%), fruits (61.2%), Andean grains (49.0%), compared to males who reported lower consumption. As for environmental behavior, respondents indicate that organic foods were healthier and more environmentally friendly to local food.